The Role of Teachers in Traditional Games for the Developme of Fine Motor Skills in Early Childhood in Kindergarten: A Heart of Kampung Baru Village: Peran Guru Dalam Permainan Tradisional Untuk Pengembangan Motorik Halus Anak Usia Dini di Taman Kanak-Kanak Sebuah Hati Desa Kampung Baru Kabupaten Batanghari - Elvi Amelia; Jamilah Jamilah; Amrindono Amrindono (The Future of Education Journal, 2026)
This study aims to describe in depth thel role ofl teachers inl developing finel motor skillsl in earlyl childhood at the Kindergarten of a Heart in Kampung Barul Village, Marol Sebo Ulul District, Batangl Hari lRegency, Jambi Province. Thisl study uses a descriptive qualitative method with datal collection techniquesl in thel form ofl direct lobservation, in-depth linterviews, andl documentation of learning activities. Thel results ofl the studyl indicate that teachersl have al very strategicl role as planners, activity implementers, learning facilitators, and evaluators of children's learning outcomes. Through congklak playing activities. Children can develop fine motor skills such as holding, moving, and dropping congklak seeds with their fingers. Supportingl factors forl the successl of this activity includel the support ofl school facilitiesl and linfrastructure, thel availability ofl traditional congklak game tools. However, teachersl also facel obstacles suchl as limitedl media, lackl of activity variations, and differences in children's ability levels. Overall, this study confirms that the active and creative role of teachers is very important in creating an interesting, innovative learning atmosphere and is able to develop finel motor skillsl in earlyl childhood.